PENGABDIAN MASYARAKAT WORKSHOP DASAR-DASAR JARINGAN KOMPUTER DI MADRASAH ALIYAH TARBIYAH ISLAMIYAH KOTA TANGERANG, BANTEN - Adam Maulana; Allen Ishak Tadeus; Churul Ain Yahya; Faried Brian Prawira; Firda Auliatunnajah; Iqbal Nurhidayat; Karen Azelia Syalom; Marco Melandri; Riko Abdi Prayasa; Aditya, Yoga (Abdi Jurnal Publikasi, 2023)
Community Service (PKM) is an activity that has a noble goal, namely making a positive and useful contribution to society without expecting anything in return. One important aspect that PKM focuses on is the application of Information and Communication Technology (ICT) to improve the quality of education. In the midst of technological developments, there are still several communities, especially in rural areas, which face limited access and understanding of the Community Service (PKM) program, namely the method of transferring knowledge from students to those being taught, with a description of the PKM method as follows. . 1. Consultation with the supervisor, to discuss starting from the preparation of the activity until the end of the activity. 2. Observations to determine the real conditions of MAS Tarbiyah Islamiyah. This observation looks at the conditions of lesson hours, school activities, and number of students. The results of the community service that we delivered to the junior Qur'an Scholar junior high school students were quite good, they already understood the material we conveyed [10] so that when they practiced, almost 87.86% of the students were able to practice according to the material we taught. .No Comprehension Material In this community service (PKM), the main focus is overcoming limited access and knowledge of Information and Communication Technology (ICT) in the Madrasah Aliyah Tarbiyah Islamiyah environment, Benda District, Tangerang City, Banten. These problems involve students who face difficulties in understanding and using technology, especially computer networks, which can affect the effectiveness of their learning in the digital era.